2017
DOI: 10.1016/j.molmet.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Global IP6K1 deletion enhances temperature modulated energy expenditure which reduces carbohydrate and fat induced weight gain

Abstract: ObjectiveIP6 kinases (IP6Ks) regulate cell metabolism and survival. Mice with global (IP6K1-KO) or adipocyte-specific (AdKO) deletion of IP6K1 are protected from diet induced obesity (DIO) at ambient (23 °C) temperature. AdKO mice are lean primarily due to increased AMPK mediated thermogenic energy expenditure (EE). Thus, at thermoneutral (30 °C) temperature, high fat diet (HFD)-fed AdKO mice expend energy and gain body weight, similar to control mice. IP6K1 is ubiquitously expressed; thus, it is critical to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 64 publications
1
65
0
Order By: Relevance
“…Previous studies from one of us showed that genetic deletion and pharmacological inhibition of IP6K1 protects mice from HFD‐induced weight gain and insulin resistance by enhancing insulin sensitivity via AKT activation, and decelerating weight gain by enhancing thermogenic energy expenditure in adipose tissue . Our current findings together with previous studies demonstrate that IP6K1 inactivation/inhibition restores glucose homeostasis and insulin sensitivity in HFD fed mice without adversely affecting bone metabolism.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous studies from one of us showed that genetic deletion and pharmacological inhibition of IP6K1 protects mice from HFD‐induced weight gain and insulin resistance by enhancing insulin sensitivity via AKT activation, and decelerating weight gain by enhancing thermogenic energy expenditure in adipose tissue . Our current findings together with previous studies demonstrate that IP6K1 inactivation/inhibition restores glucose homeostasis and insulin sensitivity in HFD fed mice without adversely affecting bone metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…Recent studies indicate that mice with a germline deletion of inositol hexakisphosphate kinase 1 ( Ip6k1 ), the major isoform of three known inositol hexakisphosphate kinases , are protected against HFD‐induced weight gain and insulin resistance . A family of three mammalian IP6 kinases (IP6Ks) primarily generates the inositol pyrophosphate 5‐IP7 from IP6 .…”
Section: Introductionmentioning
confidence: 99%
“…Such experiments have, for example, shown that IP6Ks regulate insulin secretion from pancreatic β-cells (10). IP6K1 KO mice exhibit increased adipose tissue browning, insulin sensitivity, and resistance to dietinduced obesity (11,12). Another metabolic consequence of IP6K KO is an increase in glycolysis and a reduction in mitochondrial oxidative phosphorylation (6).…”
mentioning
confidence: 99%
“…Accordingly, young, chow-fed Ip6k1-KO mice display lower plasma insulin but similar blood glucose level compared to WT, indicating mild insulin hypersensitivity in the knockouts [30], which is evident in middle-aged Ip6k1-KO mice [22]. The knockouts are also protected from high fat diet induced hyperinsulinemia, hyperglycemia, hypertriglyceridemia and NAFL [22,40]. High-fat diet induced hepatotoxicity is evidenced by increased serum levels of aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) [53,82], which are reduced in Ip6k1-KO mice [22].…”
Section: Obesity Insulin Resistance and Naflmentioning
confidence: 96%
“…As Ip6k1 is the major murine isotype, Ip6k1-KO mice were characterized first, followed by Ip6k2 and Ip6k3 knockouts ( [12,25], and references therein), whereas PPIP5Ks are currently being studied [37][38][39]. Genetic deletion of Ip6k1 or Ip6k3 or pharmacologic disruption of IP6Ks protects mice from metabolic diseases including obesity, type-2 diabetes (T2D), non-alcoholic fatty liver (NAFL), osteoporosis, myocardial infarction, ischemia reperfusion injury and aging [22,29,34,[40][41][42][43][44][45]. These discoveries drew the attention of pharmaceutical companies.…”
Section: Introductionmentioning
confidence: 99%